Using the William Flexion Training Method in Decreasing Iscialgia - Purna Luberto; Setya Rahayu; Sri Sumartiningsih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effectiveness of the William Flexion exercise method in reducing pain levels. The research method used in this study is quantitative, namely experimental research. The results in this study showed that the T value was 7.819 with the T table was 1.714, meaning that the T count > T table, meaning that using the William Flexion training method can reduce the level of ischialgia pain. This is because the movements in the William Flexion training method, such as sit-ups and flexion movements, are appropriate for people who suffer from pain. In conclusion, giving William flexion exercise is effectively applied to ischialgia patients. Keywords: Ischialgia, William Flexion Exercise, Pain